Insights into the subsurface structure of the Caloris basin, Mercury, from assessments of mechanical layering and changes in long‐wavelength topography. Issue 10 (3rd October 2013) - Klimczak, Christian; Ernst, Carolyn M.; Byrne, Paul K.; Solomon, Sean C.; Watters, Thomas R.; Murchie, Scott L.; Preusker, Frank; Balcerski, Jeffrey A.
<x xml:space="preserve">Abstract</x> [1] The volcanic plains that fill the Caloris basin, the largest recognized impact basin on Mercury, are deformed by many graben and wrinkle ridges, among which the multitude of radial graben of Pantheon Fossae allow us to resolve variations in the depth extent of associated faulting. Displacement profiles and displacement‐to‐length scaling both indicate that faults near the basin center are confined to a 4‐km‐thick mechanical layer, whereas faults far from the center penetrate more deeply. The fault scaling also indicates that the graben formed in mechanically strong material, which we identify with dry basalt‐like plains. These plains were also affected by changes in long‐wavelength topography, including undulations with wavelengths of up to 1300 km and amplitudes of 2.5 to 3 km. Geographic correlation of the depth extent of faulting with topographic variations allows a first‐order interpretation of the subsurface structure and mechanical stratigraphy in the basin. Further, crosscutting and superposition relationships among plains, faults, craters, and topography indicate that development of long‐wavelength topographic variations followed plains emplacement, faulting, and much of the cratering within the Caloris basin. As several examples of these topographic undulations are also found outside the basin, our results on the scale, structural style, and relative timing of the topographic changes have regional applicability and may be the surface expression of global‐scale interior processes on Mercury.